2013
DOI: 10.1155/2013/254529
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Acute Renal Injury in Diabetic Mice with Experimental Endotoxemia: Role of Hypoxia-Inducible Factor-1α

Abstract: The role of diabetic nephropathy in the outcome of acute renal injury (AKI) is not well defined. Herein we evaluate the outcome of lipopolysaccharide- (LPS-) induced AKI in streptozotocin-induced diabetes, as well as the potential role of Hypoxia Inducible Factor (HIF-1α) in this condition. Although 6 h after LPS injection all mice developed a decrease in renal function, proteinuric diabetic mice showed a better recovery of this parameter throughout the study (72 h). Both HIF-1α and vascular endothelium growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This therefore suggests that a better renal outcome is a consistent finding related to diabetes, rather than a difference in the nature of AKI itself. These observations are consistent with experimental studies suggesting that the diabetic state may limit acute renal injury through ‘pre‐conditioining’ and also facilitate recovery by priming regenerative mechanisms …”
Section: Discussionsupporting
confidence: 90%
“…This therefore suggests that a better renal outcome is a consistent finding related to diabetes, rather than a difference in the nature of AKI itself. These observations are consistent with experimental studies suggesting that the diabetic state may limit acute renal injury through ‘pre‐conditioining’ and also facilitate recovery by priming regenerative mechanisms …”
Section: Discussionsupporting
confidence: 90%
“…As previously viewed, hypoxia already existed in the subclinical stage of DN, and expression of HIF‐1α also increased . Ortega et al have shown that in addition to hypoxia, some factors, such as inflammation and stress, also up‐regulate the expression of HIF‐1α.…”
Section: Introductionmentioning
confidence: 99%
“…However, we observed that diabetes was not independently associated with mortality in whole AKI patients after adjusted for age, gender, and regions. The possible explanations for this phenomenon are diabetic state postponed renal injury through 'pre-conditioning' [25] and priming regeneration mechanisms [23].…”
Section: Discussionmentioning
confidence: 99%